THE INFLUENCE OF BACILLUS ARYABHATTAI SKC-5 MICROORGANISMS AND GLUTARALDEHYDE BIOSIDE ON THE CORROSION RESISTANCE OF API 5L X52 STEEL IN SEAWATER ENVIRONMENT - Albary, Ridha
Low-carbon API 5L X52 steel is an economical and practical choice for pipeline materials in the oil and gas industry due to its commendable corrosion resistance. However, the potential threat of microbiologically induced corrosion necessitates careful consideration. This research aims to investigate the impact of Bacillus aryabhattai SKC-5 bacteria and the addition of glutaraldehyde on the biocorrosion processes affecting low-carbon steel alloy immersed in a seawater environment. Specimens in the form of API 5L X52 pipes were immersed in seawater containing bacteria and glutaraldehyde for 7 and 14 days. Bacterial concentrations in the test solution were assessed using the Total Plate Count (TPC) method and Optical Density (OD) measurements. Concurrently, the corrosion behavior of the specimens in the test solution was analyzed through electrochemical testing and weight loss measurements. Corrosion product identification on the specimen surfaces was performed using Fourier Transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Scanning Electron Microscope (SEM) equipped with Energy Dispersive Spectroscopy (EDS). The research results indicate that the presence of bacteria reduces the corrosion rate on the immersed specimens by 65.13% after seven days and 90.87% after 14 days based on weight loss testing. Current density values also experienced a decrease of 3.4% after seven days and 27.57% after 14 days, according to Tafel extrapolation results. The presence of bacteria enhanced the polarization resistance values by 46.5 times after seven days of immersion and 10.6 times after 14 days. TPC test results demonstrate that glutaraldehyde significantly inhibits bacterial growth, with reductions of 95.78% for planktonic bacteria and 79.09% for sessile bacteria, along with a decrease in absorbance values based on OD testing. Concurrently, the bacterial activity led to an 8.03% reduction in carbon element dispersion during the 7-day immersion and 1.46% during the 14-day immersion. The effective presence of glutaraldehyde decreased the corrosion rate on seawater-bacteria-immersed specimens with efficiencies of 56.28% after seven days and 51.27% after 14 days, reducing corrosion current density values and enhancing specimen polarization resistance. Bacterial biofilm was confirmed via SEM-EDS testing via carbon element dispersion on the specimen surface. These findings are corroborated by identifying functional groups originating from bacteria through FTIR testing. XRD testing further confirms the oxidation of ferrous to ferric by bacteria, as evidenced by the presence of Fe+3O(OH).